Pengujian faktor anteseden pada loyalitas pengguna internet banking - Widyartono, Agustinus; Sardjono, Andreas (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2020)
This study aims to prove the influence of shared value and communication carried out by banking industry actors on the internet banking service to customer loyalty by trust mediation. The survey that will be conducted in this study includes the users of internet banking in the city of Palembang. The method that will be used in this research is to use path analysis. This research proves that the value shared and communication significantly influence trust. This study also proves that trust is a variable that mediates the effect of shared values ​​on loyalty. The communication factor in which the internet banking application is used is able to convey clear information to customers and this will increase customer confidence in the application. Besides that, customers also have and get value for internet banking applications to make customers more confident or trust in the application.